2020
DOI: 10.3390/cancers12030755
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Mitochondria Genome and Clinical Outcomes in Stage 1 Lung Adenocarcinoma

Abstract: Risk factors including genetic effects are still being investigated in lung adenocarcinoma (LUAD). Mitochondria play an important role in controlling imperative cellular parameters, and anomalies in mitochondrial function might be crucial for cancer development. The mitochondrial genomic aberrations found in lung adenocarcinoma and their associations with cancer development and progression are not yet clearly characterized. Here, we identified a spectrum of mitochondrial genome mutations in early-stage lung ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Mitochondrial biogenesis was higher in the ALT group than in the telomerase group according to a previous study [ 23 ]. The vulnerability of the mitochondrial genome to mutations and the somatic mutations promote poor prognosis [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial biogenesis was higher in the ALT group than in the telomerase group according to a previous study [ 23 ]. The vulnerability of the mitochondrial genome to mutations and the somatic mutations promote poor prognosis [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Raghav et al found that the mean germline mtDNA mutation rate in stage 1 lung adenocarcinoma was 2.29 mutations per kbp. Most of the mutations occurred in the D-loop and the CYTB gene (which are part of the mitochondrial respiratory chain) [ 149 ].…”
Section: The Role Of Mitochondria and Mtdna In The Development Of Lun...mentioning
confidence: 99%
“…A study regarding mitochondria genome in stage I pulmonary adenocarcinoma showed that patients with somatic mutations in the D-loop region had longer relapse-free survival (RFS) than those without, whereas somatic mutations in mitochondrial Complex IV and Complex V genes were related to shorter RFS [87]. In pulmonary adenocarcinoma, the NGS study also showed six potential oncogenic genes, including AGR2, SPDEF, CDKN2A, CLDN3, SFN, and PHLDA2, and seven tumor suppressor genes [88].…”
Section: Rare Mutation Other Than Egfr and Alkmentioning
confidence: 99%